Automatic generation of a PLC controller based on a control system-identified model - Sýkora, Tomáš; Husák, Michal; Benešl, Tomáš; Baštán, Ondřej (Slovak University of Technology, 2021)
This paper discusses the automatic generation of controller codes through a model created in the MATLAB environment. The aim of the research is to simplify the implementation and tuning of the closed-loop circuit in industrial systems; in this context, the concepts and steps outlined herein could produce a more intuitive and powerful alternative to the pre-defined software components of control systems that enable closed-loop control. We propose a methodology for identifying the system through an industrial control setup, creating a control loop model, and generating a code implementable in the control setup. Importantly, we also present and compare the results obtained with various variants of the automatically generated control circuit containing a pre-defined controller of the industrial control system. The outcomes of the research allow us to conclude that the implementations generated by the model perform better that the option using a built-in controller.

This paper discusses the automatic generation of controller codes through a model created in the MATLAB environment. The aim of the research is to simplify the implementation and tuning of the closed-loop circuit in industrial systems; in this context, the concepts and steps outlined herein could produce a more intuitive and powerful alternative to the pre-defined software components of control systems that enable closed-loop control. We propose a methodology for identifying the system through an industrial control setup, creating a control loop model, and generating a code implementable in the control setup. Importantly, we also present and compare the results obtained with various variants of the automatically generated control circuit containing a pre-defined controller of the industrial control system. The outcomes of the research allow us to conclude that the implementations generated by the model perform better that the option using a built-in controller.
Automatic generation of a PLC controller based on a control system-identified model
Keywords: control system; system identification; PLC code generation; Simulink PLC coder; industrial automation; control system; system identification; PLC code generation; Simulink PLC coder; industrial automation